USE OF THINK PAIR SHARE MODELS ON LEARNING TO EDIT SHORT STORY TEXTS - Nuraeni Maulida Azizah; Rima Sintia; R Ika Mustika (IKIP Siliwangi, 2019)
Learning to edit short story texts is one of the lessons that are difficult for students to master. This is evident when observing the school that students feel difficulty in applying the text according to the grammar in a writing. The purpose of this study is 1) To describe the activities carried out by teachers and students when learning to edit short story texts using the think pair share model. 2) To find out the difference between the results of the initial test and the final test of learning to edit the short story text before and after using the think pair share model. 3) To describe students' responses to learning to edit short story texts using the think pair share model. The researcher used the pre-experimental design method, while the design of this study was one group pretest-posttest design. The population and sample of the study were conducted in one class, namely class XI with samples of class XI AP 2, amounting to 30 people. The results of teacher activity data on learning to edit short story texts using the think pair share model is 92% while student activities are 95%. This shows that the activities of teachers and students run effectively. While the results of the data obtained that there is an increase in the value of students before using the think pair share model on the initial test get an average value of 50 and experience an increase after using the think pair share model on the final test with an average value of 78. There is a difference in the average value students between pretest and posttest is 28. Based on the results of the t-test, the sig value is obtained 0,000, the value is ≤ 0.05. Thus, H1 is accepted and Ho is rejected. Then it can be concluded that learning to edit short story texts using the think pair share model increases students' ability to edit short story texts.